115k views
0 votes
The value of ( 7 + 4root 3) ( 7 - 4 root 3) is​

2 Answers

6 votes


\boxed{1}


\large\mathfrak{{\pmb{\underline{\red{Step-by-step\:explanation}}{\orange{:}}}}}


(7 + 4 √(3) ) \: (7 - 4 √(3) ) \\ \\ = 7 \: (7 - 4 √(3) ) + 4 √(3) (7 - 4 √(3) ) \\ \\ = 49 - 28 √(3) + 28 √(3) - 48 \: (since \: √(3) * √(3) = 3)\\ \\ = 49 - 48 \\ \\ = 1

You can also use the identity:

( a + b ) ( a - b ) =
{a}^(2) - {b}^(2)


\large\mathfrak{{\pmb{\underline{\orange{Happy\:learning }}{\orange{!}}}}}

User John Peralta
by
5.3k points
2 votes

Answer:

Explanation:

(a + b)(a - b) = a² - b²


(7 + 4√(3)) (7 - 4√(3)) = 7^(2)-(4√(3) )^(2)\\\\ = 49 - 4^(2)*(√(3))^(2)\\\\= 49 - 16 * 3\\\\= 49 - 48\\\\= 1

User Carlos Vilchez
by
5.0k points